Approche orientee objets et hierarchie linguistique de concepts Questions d’application - Śmigielska, Beata (Neophilologica, 2004)
In the first part of the article the author focuses her attention on the presentation of the object-oriented method of lexicographic description proposed by W. Banyś. She also refers to G. Gross’ concept based on the notion of “objectivity”. She carefully considers the problem of the hierarchy of semantic concepts in the object-oriented approach and analyses the ontological semantic categories proposed by the WordNet lexical database. In the final part of the article the author presents an analysis of lexical hierarchy in the object-oriented approach. The author based her analysis on a few French verbs.